Misfit-layered Bi1.85Sr2Co1.85O7.7−δ for the hydrogen evolution reaction : beyond van der Waals heterostructures - Chua, Chun Kiang (2015)
Recent research on stable 2D nanomaterials has led to the discovery of new materials for energy-conversion and energy-storage applications. A class of layered heterostructures known as misfit-layered chalcogenides consists of well-defined atomic layers and has previously been applied as thermoelectric materials for use as high-temperature thermoelectric batteries. The performance of such misfit-layered chalcogenides in electrochemical applications, specifically the hydrogen evolution reaction, is currently unexplored. Herein, a misfit-layered chalcogenide consisting of CoO2 layers interleaved with an SrO–BiO–BiO–SrO rock-salt block and having the formula Bi1.85Sr2Co1.85O7.7−δ is synthesized and examined for its structural and electrochemical properties. The hydrogen-evolution performance of misfit-layered Bi1.85Sr2Co1.85O7.7−δ, which has an overpotential of 589 mV and a Tafel slope of 51 mV per decade, demonstrates the promising potential of misfit-layered chalcogenides as electrocatalysts instead of classical carbon.